Impact of pharmacodynamic biomarkers in immuno-oncology phase 1 clinical trials. (September 2022) - Salawu, Abdulazeez; Hernando-Calvo, Alberto; Chen, Rachel Y.; Araujo, Daniel V.; Oliva, Marc; Liu, Zhihui A.; Siu, Lillian L.
Abstract: Background: Phase 1 immuno-oncology (IO) trials frequently involve pharmacodynamic (PD) biomarker assessments involving tumour biopsies and/or blood collection, with increasing use of molecular imaging. PD biomarkers are set to play a fundamental role in early drug development of immuno-oncology (IO) agents. In the IO era, the impact of PD biomarkers for confirmation of biologic activity and their role in subsequent drug development have not been investigated. Methods: Phase 1 studies published between January 2014 and December 2020 were reviewed. Studies that reported on-treatment PD biomarkers [tissue-derived (tissue-PD), blood-based (blood-PD) and imaging-based (imaging-PD)] were analysed. PD biomarker results and their correlation with clinical activity endpoints were evaluated. Authors' statements on the influence of PD biomarkers on further drug development decisions, and subsequent citations of PD biomarker study results were recorded. Results: Among 386 trials, the most frequent IO agent classes evaluated were vaccines (32%) and PD-(L)1 inhibitors (25%). No PD biomarker assessments were reported in 100 trials (26%). Of the remaining 286, blood-PD, tissue-PD, and imaging-PD data were reported in 270 (94%), 94 (33%), and 12 (4%) trials, respectively. Assessments of more than one PD biomarker type were reported in 82 studies (29%). Similar proportions of blood-PD (9%), tissue-PD (7%), and imaging-PD studies (8%) had positive results that correlated with clinical activity. Results of 22 PD biomarker studies (8%) were referenced in subsequent clinical trials. Conclusions: Most phase 1 IO studies performed PD biomarker assessments. Overall, positive PD biomarker results were infrequently correlated with clinical activity or cited in subsequent trials, suggesting a limited impact on subsequent drug development. With emerging health regulatory emphasis on optimal dose selection based on PD activity, more informative and integrative multiplexed assays that capture the complexity of tumour-host immunity interactions are warranted to improve phase 1 IO trial methodology. Highlights: 386 Phase 1 IO trials reviewed and 74% reported PD biomarkers (PD). 94% of PD biomarkers were blood-based; 33% were tissue-based; 4% were imaging- based. Evaluation of immune cell subsets in the circulation and/or tissue were most common. Under 10% of PD correlated with clinical activity, or were subsequently referenced. With greater emphasis on dose optimization, more informative PD assays are warranted.